Impact of Covid-19 Pandemic on the Net Profit and its Principal Determinants of Nepalese Commercial Banks (Journal of Management, 2022)
COVID-19's influence on net profit and its main variables, such as net interest income, fee and commission revenue, and total operating income of Nepalese commercial banks, is explored. It also aims to determine the relationship between variables as well as the short- and long-term effects of interest income, fee and commission revenue, and operating income on commercial banks' net profit. The panel data of 27 commercial banks from 2011 (fiscal year 2010/11) to 2020 (fiscal year 2019/20) are examined and collected from the Nepal Rastra Bank's Banks Supervision Reports. The descriptive statistics, correlation analysis, panel unit root testing, and panel autoregressive distributed lag (ARDL) model are all employed. Net interest income and net profit (0.901), fee and commission income and net profit (0.823), and total operating income and net profit (0.823) all have a strong positive connection (0.800). The COVID-19 outbreak hurts commercial banks' net profits in both the short and long term. However, the research produced some disputed findings. For example, consider the long-term negative impact of total operating profit on commercial bank net profit and the short-term negative impact of net interest income on commercial bank net profit. It is suggested to decrease unneeded expenditures that may be cut without disrupting the banking business to enhance profit. The importance of e-banking might be stressed to slow the rapid decline in bank profit and other earnings. This article is unique because the researcher is not affected by other researchers' tools, methodologies, and findings.